Need Assesment Perilaku Sehat pada Mahasiswa Psikologi Angkatan 2021 Kampus V Universitas Negeri Padang - Apriyani Apriyani; Mutiara Rahma Eldita; Tiara Tri Ariani; Zakia Miftahul Faradisi; Adifa Khoiron; Nurhasni Nurhasni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Several surveys of (college) students have revealed that many of them have not adopted (accustomed) a healthy lifestyle. This is of course (surely) a concern because good health determines a good quality of life, including physical, educational, emotional and spiritual aspects. Therefore, it is important for every individual (everyone) to adopt (get used to) a healthy lifestyle, including students. This research aims to look at the healthy living behavior of students majoring in psychology at Padang State University. This research consisted of 89 students selected through purposive sampling. The measurement instrument in this study was adapted from the healthy living behavior scale in research conducted by Monika (2018) with a total of 30 questions. The results of the study showed that 8% of students were in low healthy lifestyle behavior and 55% of students were in moderate healthy lifestyle behavior.